A numerical study on the mixing quality of an electroosmotic micro-mixer with different angle internal fins (Texas Journal of Multidisciplinary Studies, 2021)
In devices with exact dimensions and low Reynolds number owing to limited flow, increasing the mixing quality is essential. In this study, he focuses on increasing the effective parameters and their impacts on the mixing quality of a two-dimensional device (active micro-mixer) (active micro-mixer). This gadget mixes the two entering liquids with varying concentrations that enter the micro-channel from two separate inlets. 6 internal fins were positioned at various angles to the y axis Four electrodes are also placed on the walls of the mixing chamber where the time-dependent electric field is applied, where the resulting electric force disturbs the parallel smooth flow lines, in addition to introducing the thermal physical property (joul heat) resulting from the magnetism generated by the electric current of the electrodes. The governing equations are solved numerically using COMSOL Multiphysics 5.5a Numerically active electro-micromixers have been investigated for various values of inlet velocity, frequency, and voltage. The findings revealed that the quality of mixing relies significantly on the angle of inclination of the fins in the direction or opposite direction of the flow, where the angle of 45 degrees is the best, followed by the angle of 30 degrees, then 0, and the last angle comes -45 degrees. The findings also indicated that the existence of vortices produced by the presence of fins makes the variations in mixing quality minimal and steady when utilizing the parameters of entrance speed, voltage, and frequency